Silver nanoparticles induce pro‐inflammatory gene expression and inflammasome activation in human monocytes. Issue 10 (10th March 2016) - Murphy, A.; Casey, A.; Byrne, G.; Chambers, G.; Howe, O.
Abstract: A complete cytotoxic profile of exposure to silver (AgNP) nanoparticles investigating their biological effects on the innate immune response of circulating white blood cells is required to form a complete understanding of the risk posed. This was explored by measuring AgNP‐stimulated gene expression of the pro‐inflammatory cytokines interleukin‐1 (IL‐1), interleukin‐6 (IL‐6) and tumour necrosis factor‐alpha (TNF‐α) in THP‐1 monocytes. A further study, on human monocytes extracted from a cohort of blood samples, was carried out to compare with the AgNP immune response in THP‐1 cells along with the detection of pro‐IL‐1β which is a key mediator of the inflammasome complex. The aims of the study were to clearly demonstrate that AgNP can significantly up‐regulate pro‐inflammatory cytokine gene expression of IL‐1, IL‐6 and TNF‐α in both THP‐1 cells and primary blood monocytes thus indicating a rapid response to AgNP in circulation. Furthermore, a role for the inflammasome in AgNP response was indicated by pro‐IL‐1β cleavage and release. These results highlight the potential inflammatory effects of AgNP exposure and the responses evoked should be considered with respect to the potential harm that exposure may cause. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : As a result of the increasing incidence of silver nanoparticle (AgNP) exposure, it is vital to determine their effect on the immune response. This study clearly demonstrates proinflammatory cytokine up‐regulation after AgNP exposure to both a THP‐1 monocyte cell line and primary human monocytes and the synergistic effect of combined exposure to AgNP and LPS. In addition, the release of IL‐1β by THP‐1 cells indicates inflammasome involvement. These results demonstrate the important immunological influence of AgNP.